A COLLABORATIVE MULTIDISIPLINES LEARNING MODEL (CoMEL) FOR STRENGTHENING STUDENTS' EMPLOYEE COMPETENCIES - Yudan Hermawan; Abdul Alim; Penny Rahmawaty; Lina Nur Hidayati; Riko Septiantoko; Kiki Irafa Candra (Program Studi PGSD Universitas Flores, 2025)
The need for graduates who are adaptive, creative, and able to create their own jobs drives the importance of innovation in entrepreneurship education in higher education. However, conventional learning approaches still focus heavily on theoretical aspects and do not develop practical skills that are relevant to the real world. This study develops the CoMEL (Collaborative Multidisciplinary Entrepreneurship Learning) learning model as an innovative framework to overcome the limitations of conventional entrepreneurship education in higher education. Conventional learning models often only emphasize cognitive aspects and ignore affective and psychomotor skills that are important in entrepreneurship. CoMEL integrates collaborative learning, experiential learning, and project-based activities to strengthen students' entrepreneurial competencies. This model was developed using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) framework and was tested on 80 students participating in the Independent Campus Entrepreneurship Program at Yogyakarta State University. The results showed that the CoMEL model was able to improve team collaboration, creativity, problem solving, prototyping, and reflective learning of students. Students were involved in multidisciplinary teamwork, developing business ideas, building and testing prototypes, and conducting final presentations equipped with structured reflections. This study concludes that CoMEL is an effective model for preparing students to navigate entrepreneurial challenges through active, collaborative, and experiential learning strategies.